The Quality of Regional Government and Firm Performance - Fernanda Ricotta (European Regional Science Association (ERSA), 2016)
The performance of a firm is influenced by decisions made by the firm itself as well as factors external to it. Firm competencies are important but also competencies that pertain to territories. External factors encompass different aspects of the environmental context in which firms operate, such as physical infrastructures, innovative capacity and efficiency of the public administration. The attention in this paper is on the effect of regional quality of government (QoG) on the Total Factor Productivity (TFP) of firms. The analysis is based on comparable cross-country data of manufacturing firms operating in the seven European countries (Austria, France, Germany, Hungary, Italy, Spain and the United Kingdom) included in the 'European Firms in a Global Economy: internal policies for external competitiveness' (EFIGE) project. The measure of the 'quality of government' is the European quality of government index (EQI), calculated at regional level over twenty-seven EU members. Scholars have demonstrated that the institutional environment affects macro variables such as growth, income level, productivity, innovation activity, investment and trade at the country (Aron 2000; Acemoglu, Johnson and Robinson, 2001; Hall and Jones, 1999; Barbarosa and Faria 2011; Levchenko 2007) as well as at the regional level (Tabellini 2010; Rodríguez-Pose and Di Cataldo 2014; Ketterer and Rodríguez-Pose 2014). The quality of institutions also influences micro variables such as firm performance (Dollar, Hallward-Driemeier, and Mengistae, 2005; Lasagni, Nifo and Vecchione, 2015; Aiello, Pupo and Ricotta, 2014; Manzocchi, Quintieri and Santoni, 2014). Recent studies indicate that there might be a significant difference in the macro- and micro-impacts of institutional quality: better institutional quality that may have beneficial macro-implications, may not necessarily have positive implications for firm performance (Bhaumik and Dimova 2014). Thus, the proper level of analysis to test whether the regional institutional environment affects productivity is to focus on firms (Beugelsdijk 2007). To disentangle internal from external productivity drivers, the multilevel approach is employed. In the econometric specification, the 2008-value of TFP depends on key-drivers of firm performance (size, family-management, group membership, innovations and human capital), on the variable of interest, the indicator of the quality of government, and on control variables at the regional level that, according to the theoretical and empirical literature, may affect firms' economic performance. Results refer to 2008 and show, as expected, the importance of firm-specific determinants of TFP. Results confirm that to be located in a region with high level of R&D and good infrastructure is correlated positively to the firm's TFP. As far as the specific scope of this paper is concerned, the quality of regional government has a positive impact on firm TFP. This is in line with previous research which underlines the importance of the quality of institutions at the regional level while it contradicts the hypothesis that within country institutional differences do not matter for economic performance (Gennaioli et al, 2013). As far as the EQI components are concerned, corruption and the quality of services appear to be positively correlated to TFP, while the evidence is inconclusive for the impartiality indicator.
Keywords: O43; D24; C30; 330; Institutions; firm performance; European regions; multilevel model